The Russian Revolution and its impact on the West: The case of the British Marxist Historians - Barrientos Valverde, Jorge (2018)
The present work develops an analysis of the work and contributions of British Marxist historians from of the impact of the Russian Revolution, study group born in the fifties, and covers the main works and theses of some of the most relevant and paradigmatic historians of this group between 1950 and the present. As hypothesis, we propose that this grouping throughout its history generates, for the chronological, the ideological, the political and the analytical, three main generations of historians and writers of great intellectual level. Each of them characterized by their motivations, interests and personal struggles, but also by the conjunctures and currents of thought and analysis that were emerging. Undoubtedly this group marked a change and a turning point paradigm in modern historiography that is worth retaking and revitalizing in our context.